Pengaruh Kualitas Produk Terhadap Loyalitas Konsumen Dengan Kepuasan Konsumen Sebagai Variabel Intervening (Studi Pada Pengguna Game Among Us) - Aldo Septa Nugraha (Journal of Economic, Bussines and Accounting (COSTING), 2023)
This research was conducted to determine the effect of product quality on consumer satisfaction and its effect on consumer loyalty in the Among Us game. Data analysis techniques using path analysis. The population in this study were users of the Among Us game in Malang City with a sample of 96 respondents who had played the Among Us game and were aged 18-35 years. Data collection techniques using a questionnaire. Meanwhile, the results of the study show that the results of product quality have a significant effect on consumer loyalty, product quality has a significant effect on visitor satisfaction, consumer satisfaction has a significant and negative role in mediating consumer loyalty and product quality. Keywords: Consumer Loyalty, Consumer Satisfaction, Product Quality